Exploring Alkali Hydroxide Influence on Calcium Titanate Formation for Application in Biodiesel Catalysts - Puntharod, Ratchadaporn; Onsomsuay, Kittikarnkorn; Pookmanee, Pusit; Kumchompoo, Jaturon (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Biodiesel has been recognized as the most widely utilized biofuel around the world due to its significant role in reducing the consumption of crude oil and lowering environmental pollution levels. By serving as a renewable alternative to fossil fuels, bioethanol helps decrease greenhouse gas emissions and contributes to a more sustainable energy future. Traditionally, alkali hydroxides like NaOH and KOH have been mainstays in biodiesel synthesis. However, their overuse can lead to unwanted byproducts and operational complexities. Since calcium titanate can occur at a strong base condition, it presents an alternative avenue worth exploring. In this study, we investigate the influence of alkali hydroxides, namely LiOH, NaOH, and KOH, on the formation of calcium titanate through hydrothermal methods, with varying heating times. We aim to understand how different hydroxides affect the synthesis process and the resultant properties of calcium titanate. We delve into the vibrational properties of Ca‒O‒Ti and Ti‒O bonds using Fourier transform infrared spectroscopy (FTIR), confirming the presence of calcium titanate (JCPDS No.42-0423) through X-ray diffractometry (XRD). This thorough characterization provides insight into the structural integrity and composition of the synthesized materials. Moreover, scanning electron microscopy (SEM) reveals the intriguing cube-like morphology of calcium titanate, offering visual evidence of its unique structure. The fatty acid methyl ester Iimpressively, our results show that calcium titanate synthesized in 7 M NaOH and KOH solutions, heated for 24 hours, emerges as a promising biodiesel catalyst. We observe fatty acid methyl ester provides the percentages of 63.67% and 90.02%, respectively, indicating the catalytic efficacy of these materials in biodiesel production. These findings not only contribute to the understanding of calcium titanate synthesis but also pave the way for a sustainable future in biodiesel production by introducing efficient and eco-friendly catalysts.